2011
DOI: 10.3748/wjg.v17.i5.633
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of cytomegalovirus infection in a series of patients diagnosed with moderate-severe ulcerative colitis

Abstract: Our preliminary results suggest that HCMV may remain in the colon after an acute colitis flare-up despite remission; it seems that the virus is not responsible for the disease relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
1
12
0
2
Order By: Relevance
“…CMV infection in patients with refractory or complicated IBD should be ruled out before aggressive immunosuppressive therapy is commenced . Some retrospective studies have reported that most CMV‐positive UC patients are non‐responders to steroids, and the prevalence of steroid resistance in CMV‐positive groups greatly exceeds than that in CMV‐negative groups (Table ).…”
Section: Increases the Risk Of Steroid Resistance In Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…CMV infection in patients with refractory or complicated IBD should be ruled out before aggressive immunosuppressive therapy is commenced . Some retrospective studies have reported that most CMV‐positive UC patients are non‐responders to steroids, and the prevalence of steroid resistance in CMV‐positive groups greatly exceeds than that in CMV‐negative groups (Table ).…”
Section: Increases the Risk Of Steroid Resistance In Ucmentioning
confidence: 99%
“…In a prospective, multicenter study 78.6% (11/14) of patients with steroid‐refractory UC and CMV infection got relief with ganciclovir treatment . Several studies have estimated antiviral efficacy in CMV‐positive steroid‐refractory UC patients, showing that there were varying remission rates among all study groups but the overall remission rate was up to 80.2% (Table ).…”
Section: Efficiency Of Anti‐cmv Treatmentmentioning
confidence: 99%
“…Similar findings have been reported previously using pp65 antigenemia and PCR-based strategies. 13,24,25,[31][32][33][34] In these studies, the sensitivity of CMV viremia ranged from 18% to 47%. Individual differences in study design, detection methods for CMV disease, and the threshold for positive serum tests are likely to account for the variability of the results.…”
mentioning
confidence: 98%
“…La antigenemia de CMV es la alternativa en sangre periférica más utilizada, corresponde a la detección de la proteína viral pp65 en leucocitos periféricos 45 . La serología para CMV no se recomienda, dada su baja sensibilidad y difícil interpretación [46][47][48] .…”
Section: Rol De Citomegalovirus En Crisis Grave De Enfermedad Inflamaunclassified
“…En pacientes con estudio positivo, la medición de carga viral en sangre o antigenemia pueden ayudar a guiar la terapia, aunque los valores de corte no son claros. La terapia antiviral sugerida es ganciclovir endovenoso por 14 días, cuya tasa de respuesta varía entre 60 y 86%; sin embargo, la evidencia está limitada a estudios observacionales de tipo cohorte 35,45,49,[51][52][53] . La respuesta se observa al quinto o séptimo día de tratamiento.…”
Section: Rol De Citomegalovirus En Crisis Grave De Enfermedad Inflamaunclassified